Asuhan Kebidanan Continuity of Care (COC) pada Ny L Umur 23 Tahun GIP0A0 di Desa Candirejo - Malisa; Isfaizah (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
Continuity of care (CoC) is a service that is achieved when there is an ongoing relationship between a woman and a midwife. Continuing care relates to the quality of service over time which requires a continuous relationship between patients and health professionals. Midwifery services must be provided from preconception, early pregnancy, during all trimesters, labor and delivery until the first six weeks postpartum which can reduce maternal and infant mortality rates for the health status of a nation. The aim of providing comprehensive midwifery care to Mrs L (Continuity of Care) includes pregnancy, delivery, postpartum, newborns and neonates up to family planning. In this research method, the author used a data collection method, namely using interviews, observation with primary and secondary data through the KIA Book, physical examination and this research began in November-March 2024, the research instrument used SOAP. Based on the results of a comprehensive case study (Continuity of Care) on Mrs L from pregnancy who was given midwifery care teaching prenatal yoga movements to reduce back pain, According to the theory of Yuliania et al., (2021) prenatal yoga movements consist of: Practicing by focusing attention (centering), Breathing (pranayama), Warming up movements, Core movements: (Stabilization consisting of movements, such as mountain pose (tadasana), tree pose (vrksasana), cow pose – cat pose (bitilasana marjarisana), stretching consisting of movements, such as neck muscle stretching, lateral standing, triangle pose, revolved head to knee pose, knee stretch, muscle stretch feet), during the birth period, midwifery care was also given Massage effeluge to reduce pain during labor because Mrs. babies like giving massage to healthy babies. Baby massage is a massage that is carried out closer to gentle strokes or tactile stimulation carried out on the surface of the skin, manipulation of body tissues or organs aimed at producing an effect on the muscle nerves and respiratory system as well as improving blood circulation (Roesli, 2018). Ny . L decided to use implant contraception. Abstrak Continuity of care (CoC) adalah pelayanan yang Masa kehamilan, persalinan , nifas , neonatus meupakan suatu keadaan fisiologis yang kemungkinan mengancam jiwa ibu , bayi bahkan menyebabkan kematian , salah satu Upaya yang dilakukan  yaitu dengan menerapkan asuhan komprehensif yang dapat mengoptimalkan deteksi dini resiko  resiko tinggi maternal dan neonatal. Tujuan dari penelitian ini adalah melakukan asuhan kebidanan komprehensif pada ibu hamil , bersalin , nifas dan neonatus di puskesmas suruh, metode yang digunakan adalah penelitian deskriptif dan jenis penelitian deskriptif yang digunakan adalah studi penelaahan kasus (Case Study), Teknik Pengumpulan data yang digunakan adalah menggunakan data Primer dan data sekunder. Data Primer diperoleh melalui wawancara, observasi dan pemeriksaan Fisik, serta dokumentasi menggunakan SOAP dengan pola piker manajemen Varney. sedangkan data Sekunder adalah data yang diperoleh dari buku KIA. Sample adalah seorang ibu hamil trimester II usia kehamilan 20 minggu 1 hari G1P0A0. Hasil asuhan yang didapat Ny.L umur 23 G1P0A0 usia kehamilan 20 minggu 1 hari dengan fisiologis, persalinan berlangsung secara normal, masa nifas berlangsung secara normal , tidak ada pendarahan , kontraksi baik, lochea rubra. Luka perineum grade 2 , ibu mendapatkan vitamin A dan mefenamic acid, dan pada bayi aru lahir selama Asuhan yang diberikan pada bayi Ny.L yang sesuai dengan kebutuhan bayi seperti pemberian pijat pada bayi sehat. Ny.L memutuskan menggunakan KB implan.